Bio-efficacy of Sulfoxaflor and Other Insecticides Against Sucking Pests of Cotton - Prasad, B. Ram (International Journal of Bio-resource and Stress Management, 2022)
The field trials were conducted for two consecutive years during kharif, 2015 and 2016 seasons at the Regional Agricultural Research Station, Warangal, Telangana, India to study the bio efficacy of sulfoxaflor and other broad-spectrum insecticides on sucking pests and natural enemies of cotton under rain fed black soils. Among the treatments, a significant (47.6%) reduction of aphids was recorded with sulfoxaflor at 100 g a.i. ha-1 followed by flonicamid at 75 g a.i. ha-1 (42.8%) and sulfoxaflor at 90 (42.8%) as compared to other treatments. The highest reduction (61.0 %) of jassid was observed in flonicamid at 75 g a.i. ha-1 followed sulfoxaflor at 90 (50.8%) as compared to other treatments. The highest reduction (30.2%) of thrips was observed in sulfoxaflor at 100 g a.i. ha-1 followed by flonicamid at 75 g a.i. ha-1 (19.8%) and sulfoxaflor at 90 (19.8%) respectively, as compared to other treatments. The highest reduction (41.9%) of whitefly was observed in buprofezin at 250 g a.i. ha-1 followed by dinotefuran at 150 g a.i. ha-1 (35.5%) as compared to other treatments. None of the insecticidal treatments has affected the abundance of the natural enemy population during both the years of study. Overall, the study further revealed that, Sulfoxaflor at 100 g a.i ha-1 and flonicamid at 75 g a.i. ha-1 have shown good efficacy against sucking pests as well as recorded the highest seed cotton yield compared to other treatments and can be used as an alternative to other insecticides in the control of Cotton sucking pests.